The influence of adding B. subtilis bacteria on the mechanical and chemical properties of cement mortar - Osama Ahmed Ibrahim; Ahmed Ibrahim Hassanin Mohamed; Wael Ibrahim; Raghda Osama Abd-Al Ftah; Shimaa R. Hamed; Sherif Fakhry M. Abd-Elnaby (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background This study investigated the effect of B. Subtilis bacteria on the properties of cement mortar. This was done by using soil samples from Sharkia, Egypt, to isolate 48 bacterial strains, after which they were cultured using the Johnson method and various media. Bacteria were then added to the cement mortar in amounts of 5% and 10% by weight to evaluate their effect on the mechanical and chemical properties of the modified mortar. Results The study examined the compressive and flexural strength of the modified mortar over time, as well as its microscopic properties and chemical composition after 28 days. The results indicated that bacterial additions of 5% and 10% increased the compressive strength of the mortar after 28 and 56 days compared to the control. A 5% bacteria concentration resulted in significant improvements in strength, showing the best concentration for increasing mortar strength. The addition of 5% bacteria significantly enhanced the early flexure strength, while the 10% showed superior long-term strength after 56 days. Scanning electron microscopy (SEM) revealed high CaCO3 deposits in the bacterial samples, indicating microbial-induced calcite precipitation that filled the small cracks and increased strength. Fourier-transform infrared spectroscopy (FTIR) confirmed the presence of hydroxyl, carbonate, and silicate groups, with bacterial samples having a higher carbonate content, indicating an increase in calcium carbonate formation and microstructure. Conclusions The ideal bacterial concentration was 5% as it improved the compressive and flexural strength while also promoting a more flexible microstructure. This study supports the employment of microorganisms in the production of more durable and environmentally friendly building materials, enhancing the sustainability of building practices.